Dreamsnake - McIntyre, Vonda N. (Open Road Media, 2021)
When the healer Snake was summoned, she traveled the blasted landscape with her three serpents. From the venom of two of them, she distilled her medicines. But most valued of all was the alien dreamsnake, whose bite could ease the fear and pain of death. When the dreamsnake is killed, Snake's powers as a healer are all but lost. Her only hope of finding another dreamsnake lies in a treacherous journey to the far-off Center City, where Snake will be pursued by two implacable followers: one driven mad by love, the other by fear and need.